Islamic Education and the Challenges of Globalization: Adaptation and Innovation in Contemporary Islamic Education Movements - Yudin Citriadin; Hendy Aldian; Fahmi Parmansyah (Electronic Journal of Education, Social Economics and Technology, 2025)
The objectives of this research include: 1) to explain contemporary Islamic education, and 2) to explain the adaptation and innovation of contemporary Islamic education in facing the challenges of the globalization era. This research approach is qualitative with a literature-based method. Data sources refer to two aspects: primary data sources and secondary data sources. Primary data is data directly related to the research object, namely creativity and innovation in the development of human resource management in Islamic schools. Secondary data comes from books, journals, or references that support this research. The data collection technique used is literature review, while the data analysis technique is content analysis, consisting of data analysis and data interpretation stages. The results of this research include: 1) Contemporary Islamic education is a value-based educational system that integrates social community values, customs, culture, and other aspects as a form of preparation for facing global challenges and the era of globalization. 2) Contemporary Islamic education requires adaptation and innovation to create better quality or standard improvements in Islamic education. Forms of adaptation and innovation that can be implemented in contemporary Islamic education include: a) Integration of Technology in Learning, b) Globally Competent-Based Curriculum, c) Innovative Learning Approaches, d) Development of Soft Skills, e) International Collaboration, f) Enhancement of Teacher Competence, Contextual and Applicative Learning, and g) Supporting Infrastructure and Facilities. The implications of this research are expected to bring about better changes to the Islamic education system by referring to the results of this study.